2022
DOI: 10.3390/nu14153016
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Physical Fitness and Nutritional Status among School-Aged Children and Adolescents during the COVID-19 Pandemic in Shaanxi, China—A Cross-Sectional Study

Abstract: Background: This study aimed to explore the characteristics of trends in physical fitness and nutritional status among school-aged students during the COVID-19 pandemic, which could help to develop targeted guidelines and policies for students (adolescents) to promote health during lockdowns resulting from public health emergencies. Methods: The physical fitness and nutritional status were measured from 2019 to 2021; the correlation between years and grade were analyzed. Results: a declining trend was found in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Third, because of the impact of COVID-19, students devoted more time to taking courses online, which resulted in increased access to digital media devices and decreased physical activity time. 68 , 69 The extrapolation of our results is limited and future studies should further track observations in a broader population. Finally, although our study has controlled for several confounding factors, there are still some confounders which are difficult to measure (eg, physical and chemical environment, immunization) that may interfere with the results, and future studies should set up better-designed protocols.…”
Section: Discussionmentioning
confidence: 82%
“…Third, because of the impact of COVID-19, students devoted more time to taking courses online, which resulted in increased access to digital media devices and decreased physical activity time. 68 , 69 The extrapolation of our results is limited and future studies should further track observations in a broader population. Finally, although our study has controlled for several confounding factors, there are still some confounders which are difficult to measure (eg, physical and chemical environment, immunization) that may interfere with the results, and future studies should set up better-designed protocols.…”
Section: Discussionmentioning
confidence: 82%
“…Our results are in agreement with previous studies performed in Chinese children and adolescents (aged 6-22 years). The authors showed that the performance of muscular strength (sit-ups and pull ups), flexibility (sit and reach) and vital capacity increased while middle-distance race decreased during the pandemic (42,43).However, contrary results have been found in adolescent population across many countries (44,45), where greater reductions were observed in most physical fitness. These contradictory results could be partly influenced by the differences in evaluating physical ability across different countries, and inconsistent participant age stages in previous studies were another determinant.…”
Section: Discussionmentioning
confidence: 95%
“…Meanwhile (Rasmin et al, 2023) emphasize the need to explore the relationship between nutritional status, physical activity, type of work, and smoking activity with fitness levels. Citation (Lu et al, 2022) explores trends in physical fitness and nutritional status among school-aged children. the relationship between nutritional deficits and physical performance in the elderly has been explored and revealed mixed findings in the literature (Lu et al, 2021).…”
Section: Discussionmentioning
confidence: 99%